Modeling Analysis of Guided Ultrasonic Waves in Composite Plates with Impact Damage - Asyikin Ibrahim, Noorfaten; Intan Suraya Murat, Bibi (International Journal of Engineering and Technology, 2018)
This paper investigates the propagation of guided ultrasonic waves and the interaction with impact damage in composite plates using a full three-dimensional Finite Element analysis. Impact damage in the composite plate was modeled as rectangular- and T-shaped delaminations. In order to provide guidelines for extending the modeling of realistic multimode impact damage, the impact damage was modeled as a combination of the delamination and reduced materials properties. The information obtained from these methods was compared to the experimental results around the damage area for a validation. There was a reasonable similarity between the experimental and FE results. The FE simulations can effectively model the scattering characteristics of the A0 mode wave propagation in anisotropic composite plates. This suggests that the simplified and easy-to-implement FE model could be used to represent the complex impact damage in composite plates. This could be useful for the improvement of the FE modeling and performance of guided wave methods for the in-situ NDE of large composite structures.Â